Puerarin Alleviates UUO-Induced Inflammation and Fibrosis by Regulating the NF-κB P65/STAT3 and TGFβ1/Smads Signaling Pathways - Wang J; Ge S; Wang Y; Liu Y; Qiu L; Li J; Huang X; Sun L (Dove Medical Press, 2021)
Jingyu Wang,1 Shuke Ge,2 Yaqing Wang,1 Yi Liu,3 Lihua Qiu,4 Junying Li,4 Xin Huang,1 Li Sun1 1Department of Nephrology, The First Affiliated Hospital of China Medical University, Shenyang, 110000, Liaoning Province, People's Republic of China; 2Department of Emergency management, Liaoning Center for Disease Control and Prevention, Shenyang, 110000, Liaoning Province, People's Republic of China; 3Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, Sichuan Province, People's Republic of China; 4Department of epigenetics, China Medical University, Shenyang, 110000, Liaoning Province, People's Republic of ChinaCorrespondence: Li SunThe First Affiliated Hospital of China Medical University, North Nanjing Street 155#, Heping District of Shenyang, Liaoning Province, 110000, People's Republic of ChinaTel +86 24-83282506Email sunlicmu1974@163.comPurpose: Puerarin (PR), a Chinese medicine rich in natural components, has been reported to display anti-fibrotic, antioxidant, anti-inflammatory and immunomodulatory properties. However, the protective mechanism of PR against unilateral ureteral obstruction (UUO)-mediated renal injury is not fully clarified. Therefore, the aim of this study was to investigate the effects of PR on UUO mice and its possible mechanisms.Methods: A total of 32 C57BL/6 mice were divided randomly into four groups (n=8): i) sham-operated group (Sham); ii) UUO group (UUO); iii) UUO + PR 50 mg/kg/day (UUO + PRL); and iv) UUO + PR 100 mg/kg/day (UUO + PRH). Continuous gavage administration for 14 days starting one week postoperatively, while the mice in Sham and UUO groups were given equal amounts of vehicle by the same means. All mice were then sacrificed and serum, 24-hour urine and tissue specimens were collected for renal function, histopathology, Western blot, immunohistochemistry.Results: Renal function and histopathology revealed that PR improved UUO-mediated renal dysfunction and partially reversed tubular injury and tubulointerstitial fibrosis. Additionally, according to the results of Western blot and immunohistochemistry, PR inhibited the expression of inflammatory factors including IL-1β, IL-6, MCP-1 and ECM-related proteins including α-SMA, COL I and VIM. More importantly, the expression of fibrotic pathways TGF-β 1, Smad3, p-Smad3 and inflammatory pathways NF-κB p65, NF-κB p-p65, STAT3, p-STAT3 were inhibited to various extents under the PR treatment, while Smad7 was upregulated.Conclusion: These findings indicate that PR may inhibit the recruitment of inflammatory factors and extracellular matrix (ECM) deposition through the regulation of the NF-κB p65/STAT3 and TGFβ 1/Smads pathways, which alleviates the UUO-induced inflammatory and fibrotic response, thereby reversing renal injury.Keywords: puerarin, UUO, CKD, inflammation, fibrosis